2014
DOI: 10.1159/000361079
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mirabegron in Overactive Bladder: A Systematic Review and Meta-Analysis

Abstract: Objective: To present a systematic review assessing the efficacy and safety of mirabegron for overactive bladder (OAB). Materials and Methods: A literature search was performed using the Cochrane Library, MEDLINE, EMBASE and Science Citation Index Expanded. The literature reviewed included meta-analyses, randomized and nonrandomized prospective studies. We utilized mean difference (MD) to measure the mean number of incontinence episodes and the mean number of micturitions, and OAB questionnaire (OAB-q) and odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…Consistent with our present findings, three systematic reviews found mirabegron had similar efficacy to most antimuscarinics [34][35][36] and, where studied, all were more efficacious than placebo in reducing the frequency of UI and micturitions [35,36]. In contrast, another meta-analysis showed mirabegron to be more effective than tolterodine in the number of UIE/day, but not for micturition frequency [37]. A systematic review of non-antimuscarinic treatments for OAB, including lifestyle changes, found only one study each of onabotulinumtoxinA and mirabegron compared with active treatment [38].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our present findings, three systematic reviews found mirabegron had similar efficacy to most antimuscarinics [34][35][36] and, where studied, all were more efficacious than placebo in reducing the frequency of UI and micturitions [35,36]. In contrast, another meta-analysis showed mirabegron to be more effective than tolterodine in the number of UIE/day, but not for micturition frequency [37]. A systematic review of non-antimuscarinic treatments for OAB, including lifestyle changes, found only one study each of onabotulinumtoxinA and mirabegron compared with active treatment [38].…”
Section: Discussionsupporting
confidence: 89%
“…As dry mouth is the most bothersome TEAE related to antimuscarinic therapies, Mir might represent a valid option for the treatment of these patients. The present results confirm a previous meta‐analysis on six RCTs in which Mir showed a similar incidence of AEs when compared with a placebo, and a lower adverse reaction rate than Tol (OR 0.9; P = 0.04) . Furthermore, antimuscarinics can also contribute to a patient's anticholinergic cognitive burden, so the Beers Criteria recommends cautious use of antimuscarinics in elderly patients who take multiple anticholinergic medications or have cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
“…Another systematic review and meta‐analysis of six RCTs (BLOSSOM, DRAGON, SCORPIO, ARIES, CAPRICORN and TAURUS) showed that Mir was more effective in terms of the mean number of incontinence episodes per 24 h, although there were no differences between Mir and Tol in the mean number of micturitions per 24 h …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews and meta-analyses have evaluated the use of medications in the treatment of OAB (Chapple et al, 2015; Chapple et al, 2008; Cui et al, 2014; Herbison et al, 2003; Huang et al, 2015; Kessler et al, 2011; Luo et al, 2012; Madhuvrata et al, 2012; Novara et al, 2008; Paquette et al, 2011; Reynolds et al, 2015; Roxburgh et al, 2007; Wu et al, 2014; Wyndaele et al, 2014). These reviews compared OAB medications to placebo and/or to other OAB medications, either directly or indirectly, using prospective randomized, non-randomized, and retrospective observational trials.…”
Section: Introductionmentioning
confidence: 99%